Toward a self-reliant South: trading its way out of a long crisis - Hardy, Chandra (North-South Institute OttawaCA, 1990)
Argues for a reviewed effort at South-South cooperation. Examines the scope for increased trade, the obstacles that have stood in its way, and the measures that have to be taken by developing countries to reorient their development strategies toward internal markets and new expert markets in the South.